Состояние разработок двухфазных систем терморегулирования космических аппаратов - Турна, Рустем Юсуфович; Годунов, Артем Михайлович (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2021)
The progress of space technology is leading to more and more energy-equipped spacecraft. The International Space Station already has the capacity of solar panels of more than 100 kW. Autonomous spacecrafts and satellites (including stationary ones) have the capacity of power units of kW, in the nearest future - more than 10 kW. Forced heat transfer using single-phase liquid coolants is still considered as the main method of thermal control on high-power spacecraft (SC). Single-phase mechanically pumped fluid loop is a fully proven means of thermal control of spacecraft with a moderate heat load. A significant disadvantage of such systems is that the coolant temperature varies significantly within the loop. The temperature difference can be reduced by increasing the coolant flow rate, but for this, it is necessary to increase the pump capacity, which inevitably leads to an increase in power consumption, pipeline diameters, and weight of the system as a whole. In the case of spacecraft with high power capacity (more than 5-10 kW) and large heat transfer distances (10 m and more), a two-phase mechanically pumped fluid loop for thermal control is more preferable in terms of weight, the accuracy of thermoregulation, power consumption (and other parameters). The use of a two-phase loop (2PMPL) as a spacecraft thermal control system allows to reduce significantly mass and power consumption for own needs in comparison with a single-phase thermal control system (TCS). The effect is achieved due to the accumulation of transferred heat in the form of latent heat of vaporization and intensification of heat exchange at boiling and condensation of coolant. The article provides a critical review of published works on 2PMPL for spacecraft with high power (more than 5...10 kW) and a large heat transfer distance (more than 10...100 meters) from 1980 up to nowadays. As a result, a list of the main problems on the way of practical implementation of two-phase loops is formed.